International research-to-practice conference "Symbolic dimensions of visual culture" - Y. O. Butsykina (Ukrainian Cultural Studies, 2019)
From October 11 to 12, 2019, the international scientific conference "Symbolic Dimensions of Visual Culture" was held in the city of Lutsk (Ukraine). The event was organized by the Korsaki Museum of Modern Ukrainian Art and the Department of Ethics, Aesthetics and Cultural Studies of Taras Shevchenko National University of Kyiv within the framework of the research theme "Visual Practices: Modes and Strategies of Postmodernism" and the art project "Modern Ukrainian Symbolism", curated by Associate Professor Department S. P. Stoyan. Partners of the conference were the University of Zielona Gora (Poland), the Polish-Ukrainian Center for Humanitarian Studies of the University of Zielona Gora (Poland) and the Public Organization "Art Center Alter Ego".